2012
DOI: 10.1111/j.1574-6941.2011.01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of methanogens and identification of Methanolobus sp. as active methylotrophic Archaea in Lonar crater lake sediments

Abstract: Soda lakes constitute extreme aquatic ecosystems with remarkably high primary productivity rates, but information on the diversity and activity of methanogens in such environments is sparse. Using 16S rRNA and functional genes, we investigated the diversity of methanogens in the sediments of Lonar Lake, a unique saline and alkaline ecosystem formed by meteorite impact in the Deccan basalts. Although domain and phylum level 16S rRNA gene libraries were dominated by phylotypes related to Halobacteriales, sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 56 publications
1
25
1
2
Order By: Relevance
“…Methanogenic species related to Methanosarcina, Methanocalculus and Methanoculleus have also been isolated from the Lonar Lake sediments (Thakker and Ranade, 2002;Surakasi et al, 2007). Primer sets targeting 16S rRNA genes and mcrA (encoding the a-subunit of methyl coenzyme M reductase) revealed the presence of several potentially novel methanogenic Archaea (Methanosarcinales and Methanomicrobiales) in Lonar Lake sediments (Antony et al, 2012b). Analysis of mcrA transcripts that were retrieved from methanol-consuming and methane-emitting sediment microcosms implicated Methanolobus-like organisms as the active Archaea involved in methylotrophic methanogenesis (Antony et al, 2012b).…”
Section: Microbial Diversity Of Lonar Lake and Other Soda Lakesmentioning
confidence: 99%
See 2 more Smart Citations
“…Methanogenic species related to Methanosarcina, Methanocalculus and Methanoculleus have also been isolated from the Lonar Lake sediments (Thakker and Ranade, 2002;Surakasi et al, 2007). Primer sets targeting 16S rRNA genes and mcrA (encoding the a-subunit of methyl coenzyme M reductase) revealed the presence of several potentially novel methanogenic Archaea (Methanosarcinales and Methanomicrobiales) in Lonar Lake sediments (Antony et al, 2012b). Analysis of mcrA transcripts that were retrieved from methanol-consuming and methane-emitting sediment microcosms implicated Methanolobus-like organisms as the active Archaea involved in methylotrophic methanogenesis (Antony et al, 2012b).…”
Section: Microbial Diversity Of Lonar Lake and Other Soda Lakesmentioning
confidence: 99%
“…Primer sets targeting 16S rRNA genes and mcrA (encoding the a-subunit of methyl coenzyme M reductase) revealed the presence of several potentially novel methanogenic Archaea (Methanosarcinales and Methanomicrobiales) in Lonar Lake sediments (Antony et al, 2012b). Analysis of mcrA transcripts that were retrieved from methanol-consuming and methane-emitting sediment microcosms implicated Methanolobus-like organisms as the active Archaea involved in methylotrophic methanogenesis (Antony et al, 2012b). These methanogens may be linked to the 'intermediary ecosystem metabolism' of Lonar Lake sediments, that is, the anaerobic network of trophically linked microbes that yield intermediates (for example, fatty acids and alcohols) that drive methanogenesis either directly or indirectly (McInerney and Bryant, 1981;Drake et al, 2009).…”
Section: Microbial Diversity Of Lonar Lake and Other Soda Lakesmentioning
confidence: 99%
See 1 more Smart Citation
“…High densities of bacterial and archaeal blooms may even cause the coloration of water basins associated with the soda soils, for example, as in Magadi Lake (Kenya) due to massive expansion of red haloalkaliphilic Archaea (Jones et al 1998). Studies of 16S rDNA gene sequences revealed a complex phylogenetically heterogeneous structure of the bacterial communities inhabiting soda lakes (Duckworth et al 1996;Rees et al 2004;Dong et al 2006;Wani et al 2006) often with the recovery of many new bacterial species (Sorokin and Muyzer 2010;Sorokin et al 2011;Kompantseva et al 2012;Antony et al 2012). The accumulated data suggest that soda lakes in diverse geographical regions harbor alkaliphilic bacteria and Archaea from all major trophic groups (Rees et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports used the primers designed by Luton et al (2002) producing amplicons between 464 and 491 bp, which were analyzed and consequently excised from the DGGE gel (Antony et al 2012;García-Maldonado et al 2015). Our new alternative approach, which used semi-nested PCR coupled with the construction of clone libraries, allowed the production of longer mcrA sequences (approx.…”
Section: Resultsmentioning
confidence: 99%